The sound of porosity: Suitability of the impulse excitation technique (IET) to determine the Young's modulus of 2D macroporous ceramics - Stötzel, Tim; Funk, Swantje; Fey, Tobias (Open Ceramics, 2024)
The presence of pores in a ceramic leads to a lower Young's modulus compared to dense material. For the development of porous ceramics with tailored elastic properties, an exact determination of the Young's modulus is required, especially for industrial applications. Therefore, we investigated the suitability of the non-destructive impulse excitation technique for measuring the dynamic Young's modulus of two-dimensional ceramics with low porosity (P < 19 %). For rectangular samples it was shown that the measurement results depend on the geometric pore position, as added pores outside the nodal lines of the fundamental flexural vibration had no influence on the result. Pores in the inner part of the sample led to a decrease of the Young's modulus that is in good agreement with empirical and analytical models. For the investigated interval of porosity range, the influence of pore size and geometric position on the reduction of the Young's modulus was determined.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Impulse excitation technique; Porosity; Young's modulus